PERAN WANITA JAWA DALAM SERAT WULANG ESTRI DI ERA REVOLUSI INDUSTRI 4.0 - Sri Mulyani; NFN Mulyana (Widyaparwa, 2022)
The role of Javanese women as a companion and responsible for the survival of family life. Serat Wulang Estri was one of the works of Javanese literature which contains the advices or teachings of a father to his daughter. This contains about the attitude of women who have been married to husbands who should be taught to Javanese women since they were teenagers. The concept of Javanese women in general society tends to see women as human beings who have roles behind or called "kanca wingking" in Javanese culture. This study will describe the role of Javanese women listed on Serat Wulang Estri in families and communities in the era of the 4.0 Industrial Revolution. The research method used is a qualitative descriptive research and modern philology. Data collection is done by reading the script and then done transliteration and paraphrase in Indonesian language. The instruments used are data cards that are then analyzed in a qualitative descriptive and test the validity of the data using interater. The results of the research obtained were the role of women who have a husband who is a life companion and the responsibility of household sustainability denoted by the jempol, panuduh, panunggul, jari manis, and jenthik in the era of industrial revolution 4.0. The industrial revolution 4.0 is related to three main characters, namely innovation, automation, and digital-based information transfer. This research can be used to reference the attitude of married women to participate in the family by following the development of the era.The role of Javanese women as a companion and responsible for the survival of family life. Serat Wulang Estri was one of the works of Javanese literature which contains the advices or teachings of a father to his daughter. This contains about the attitude of women who have been married to husbands who should be taught to Javanese women since they were teenagers. The concept of Javanese women in general society tends to see women as human beings who have roles behind or called "kanca wingking" in Javanese culture. This study will describe the role of Javanese women listed on Serat Wulang Estri in families and communities in the era of the 4.0 Industrial Revolution. The research method used is a qualitative descriptive research and modern philology. Data collection is done by reading the script and then done transliteration and paraphrase in Indonesian language. The instruments used are data cards that are then analyzed in a qualitative descriptive and test the validity of the data using interater. The results of the research obtained were the role of women who have a husband who is a life companion and the responsibility of household sustainability denoted by the jempol, panuduh, panunggul, jari manis, and jenthik in the era of industrial revolution 4.0. The industrial revolution 4.0 is related to three main characters, namely innovation, automation, and digital-based information transfer. This research can be used to reference the attitude of married women to participate in the family by following the development of the era. Keywords: Role of Javanese women; Serat Wulang Estri; Industrial Revolution 4.0AbstrakPeran wanita Jawa sebagai pendamping suami dan penanggung jawab keberlangsungan kehidupan keluarga. Serat Wulang Estri merupakan salah satu hasil karya sastra Jawa yang memuat tentang piwulang atau ajaran seorang ayah kepada anak perempuannya. Piwulang tersebut berisi tentang sikap wanita yang sudah berumah tangga kepada suami yang seharusnya diajarkan kepada wanita Jawa sejak masih remaja. Konsep wanita Jawa dalam masyarakat umum cenderung melihat wanita sebagai manusia yang mempunyai peran domestik atau disebut “kanca wingking” dalam budaya Jawa. Penelitian ini akan mendeskripsikan peran wanita Jawa yang tercantum pada Serat Wulang Estri dalam keluarga dan masyarakat di era revolusi industri 4.0. Metode penelitian yang digunakan adalah penelitian kualitatif deskriptif  dan filologi modern. Pengumpulan data dilakukan dengan membaca naskah kemudian dilakukan transliterasi dan parafrase dalam bahasa Indonesia.  Instrumen yang dipakai berupa kartu data kemudian dianalisis secara deskriptif kualitatif dan uji validitas data dengan cara interater. Hasil penelitian yang diperoleh ialah peran wanita yang sudah bersuami yaitu menjadi pendamping hidup dan penanggung jawab keberlangsungan rumah tangga yang dilambangkan dengan jempol, panuduh, panunggul, jari manis, dan jenthik pada era revolusi industri 4.0. Revolusi industri 4.0 ini berkaitan dengan tiga kakater utamanya yaitu inovasi, otomasi, dan transfer informasi yang berbasis digital. Penelitian ini dapat digunakan untuk referensi sikap wanita yang sudah menikah untuk berperan dalam keluarga dengan mengikuti perkembangan jaman.